2012
DOI: 10.1001/archgenpsychiatry.2012.132
|View full text |Cite
|
Sign up to set email alerts
|

National Prevalence of Posttraumatic Stress Disorder Among Sexually Revictimized Adolescent, College, and Adult Household-Residing Women

Abstract: Context Despite empirical links between sexual revictimization (i.e., experiencing two or more sexual assaults) and posttraumatic stress disorder (PTSD), no epidemiological studies document the prevalence of sexual revictimization and PTSD. Establishing estimates is essential to determine the scope, public health impact, and psychiatric sequelae of sexual revictimization. Objective Estimate the prevalence of sexual revictimization and PTSD among three national female samples (adolescent, college, adult house… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
125
3
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(143 citation statements)
references
References 29 publications
13
125
3
2
Order By: Relevance
“…This participant described the experience of trauma symptoms identified as outcomes of victimisation (Stimmel et al, 2014;Walsh et al, 2012), as a barrier to engagement with Victim Support, consistent with previous research (Alvidrez et al, 2008;Posick, 2014).…”
Section: Suffer From Depression Anyway So That Made It a Lot Worse supporting
confidence: 78%
“…This participant described the experience of trauma symptoms identified as outcomes of victimisation (Stimmel et al, 2014;Walsh et al, 2012), as a barrier to engagement with Victim Support, consistent with previous research (Alvidrez et al, 2008;Posick, 2014).…”
Section: Suffer From Depression Anyway So That Made It a Lot Worse supporting
confidence: 78%
“…11 This is justifiable, but given the high prevalence of revictimization in women with abuse histories, 16 it may be equally important for future studies to examine the cumulative effects of trauma on CVD. Because multiple forms of trauma often co-occur (eg, child abuse, witnessing violence, and experiencing an assault as an adult), it is possible that some women experience repeated exposure to traumas, which could create more physiological "wear and tear"…”
Section: Editorial See P 251mentioning
confidence: 99%
“…In a study which examined 1915 retrospective cases, the ratio of SR was found to be 11.1% (Pittenger, 2016). In another study, the ratio of SR in female adolescents was reported to be 52.7% (Walsh, Danielson, McCauley, Saunders, Kilpatrick, & Resnick, 2012). According to the study of Humphrey and White (2000), the possibility of experiencing SA in adolescence for those who experienced SA before the age of 14, increases in 1.8 fold.…”
Section: Introductionmentioning
confidence: 98%